Microstructural and mechanical properties of ultrasonically assisted titanium-steel dissimilar metal fusion welds - Xiaohu Hao; Xinlong Wei; Shuhua Li; Zeqin Cui; Dejun Yan; Weiguo Li (Journal of Materials Research and Technology)
The formation of titanium-iron compounds during the fusion welding of titanium steels continues to pose a significant challenge. In this paper, pure copper filler wire was employed in TIG welding to join TC4 titanium alloy and 304 stainless steel. The solidification behavior of the titanium-steel molten weld interface and the morphological distribution of the brittle phase were controlled by introducing a low-power ultrasonic energy field to assist the welding process. Results indicated that the low-power ultrasonic energy field enhanced the diffusion of joint elements, leading to biased aggregation of brittle phases on the titanium and steel sides, thereby reducing the joint's mechanical properties. The high-frequency vibration produced by the increased ultrasonic power resulted in a slower diffusion of the concentration gradient, creating a more homogeneous distribution of the Ti–Fe brittle phase in the Cu interlayer. This improved the joint properties and results in the middle of the weld consisting mainly of a discontinuous Ti–Fe phases. Additionally, the distribution of the Ti–Cu phase and α-(Fe,Cr) phase became more uniform. The high-frequency vibration effectively reduced the residual stresses in the titanium-steel joints, thereby enhancing the overall performance. The tensile strength of the joints reached up to 346 MPa, an increase of 12.7% compared to before ultrasonic vibration was added.